ELECTRICAL AND MAGNETIC-PROPERTIES OF THE TL-SR-V-O SYSTEM - Liu, R; Johnson, J; Edwards, P (1991)
We report here detailed studeis of resistive and magnetic anomalies in the Tl-Sr-V-O system. Results are presented from samples with a nominal composition of TlSrVOv and reduced in an atmosphere of 5% hydrogen in argon: such materials exhibit a remarkable range of electrical properties including metal-to-metal and metal-to-semiconductor transitions. The corresponding range of magnetic properties encompass paramagnetism, antiferromagnetism and ferrimagnetism: the latter could easily be taken to be Meissner diamagnetism. These characteristic electrical and magnetic properties are extremely sensitive to sample preparation conditions; they also change with the ageing of the sample. Although a sharp drop in resistivity was observed at 160 K for certain samples, zero resistance was never observed, even when the sample was cooled to 5 K. Based on our present results, we can rule out superconductivity above 5 K in the Tl-Sr-V-O system, but we also emphasise here the remarkable variation in electronic and magnetic properties that can arise from quite modest changes in synthesis conditions of the title system.